2015
DOI: 10.1080/02705060.2015.1015109
|View full text |Cite
|
Sign up to set email alerts
|

Diet and food resource partition among benthic tadpoles of three anuran species in Atlantic Forest tropical streams

Abstract: The study of the diet of tadpoles can provide important information about the maintenance and dynamics of populations and communities of tropical amphibians. Tadpoles are in general herbivores and consume mostly algae. Despite this, little is known about how specific guilds use resources that are available in the same space and at the same time. It is thought that species of tadpoles segregate based on food use, especially in lotic environments where food resources may be a limiting factor. Conversely, it is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Under experimental conditions, they dominated under low pH values (Müller, 1980). They are very abundant in aquatic systems and important in the diets of other trophic levels, such as zooplankton (Liu and Wu, 2016) and tadpoles (Souza-Filho et al, 2007;Santos et al, 2016). Tadpoles can also be opportunistic and exploit nutritious food items that become available to them at different periods or habitats (Petranka and Kennedy, 1999;Schiesari et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Under experimental conditions, they dominated under low pH values (Müller, 1980). They are very abundant in aquatic systems and important in the diets of other trophic levels, such as zooplankton (Liu and Wu, 2016) and tadpoles (Souza-Filho et al, 2007;Santos et al, 2016). Tadpoles can also be opportunistic and exploit nutritious food items that become available to them at different periods or habitats (Petranka and Kennedy, 1999;Schiesari et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Barrio 1970, De Sá and Lavilla 1997, Kwet 2000, there is little information on the trophic ecology of the larvae (Arias et al 2002, Vera-Candioti 2007. Consequently, little is known about the role species of tadpoles in aquatic environments (Santos et al 2016).…”
mentioning
confidence: 99%
“…A recent study by Santos, Protazio, Moura, and Junca (2016) on the diet of three benthic species of Neotropical hylids (Aplastodiscus cavicola, Aplastodiscus sibilatus, and Bokermannohyla capra) identified over 1,000 distinct food items distributed across 20 taxonomic categories. This study showed overlap of approximately 16 food categories found in the guts of the three species, with algae and protozoa exhibiting the highest frequencies of occurrence in tadpole diets.…”
Section: Gut Contents Analysismentioning
confidence: 99%